A novel technique to design cuckoo search based FOPID controller for AVR in power systems. (August 2018) - Sikander, A.; Thakur, P.; Bansal, R.C.; Rajasekar, S.
Abstract: Firstly, this paper develops a robust fractional order proportional integral derivative (FOPID) controller for automatic voltage regulator (AVR) in power systems. In the proposed controller, optimum design parameters, such as, proportional, integral, derivative gains, integral and derivative constants, have been achieved by using cuckoo search (CS) algorithm. Then, the time response characteristics of AVR with and without proposed controller have been investigated to reveal the effectiveness of the proposed controller. Also, the performance of the proposed controller has been tested under the condition of the parameter uncertainty and improved performance has been revealed. Finally, the accuracy and robustness of the proposed controller has been investigated through the comparative analysis of the results, achieved from proposed and other existing controllers using the same sets of data. It is shown that the proposed controller provides the better time response characteristics than the other existing techniques.